Clinical Examination and Scoring Systems in Diabetic Peripheral Neuropathy: A Narrative Review - Suchitra Dube; Sandip M. Hulke; Santosh Laxman Wakode; Lakshya Bhardwaj (Journal of Public Health and Primary Care, 2026)
Abstract Diabetic peripheral neuropathy (DPN) is a prevalent and disabling complication of diabetes mellitus, manifesting as sensory, motor, and autonomic dysfunction. It increases the risk of foot ulceration, amputation, and cardiovascular morbidity. While nerve conduction studies (NCSs) and autonomic function testing (AFT) are considered reference standards, their high cost and limited accessibility restrict widespread use in clinical practice. This narrative review integrates findings from Indian and international literature, covering the prevalence, pathophysiology, clinical features, diagnostic methods, and recent advances in DPN assessment, including evidence from peer-reviewed articles, clinical trials, and guidelines. The prevalence of DPN in India ranges between 19% and 32% in the south, 25% and 30% in the north, and 24% and 30% in eastern regions. Clinical examination methods such as monofilament testing, vibration sense assessment, ankle reflex evaluation, and pinprick sensation, when used with validated tools such as the Michigan Neuropathy Screening Instrument (MNSI), Diabetic Neuropathy Symptom Score (DNS), Diabetic Neuropathy Examination (DNE), and COMPASS-31, demonstrate moderate-to-strong correlation with NCS and AFT. NCS provides early evidence of large-fiber involvement, while AFT evaluates cardiac autonomic function. Advanced techniques such as corneal confocal microscopy, skin biopsy, and sudomotor testing show promise but remain impractical for routine screening. Clinical examination and scoring systems are essential, cost-effective tools for the frontline detection of DPN, and combining simple bedside tests with validated questionnaires enhances early identification. There is a need for multicentric Indian studies comparing these tools with electrophysiological tests and for validating emerging diagnostic modalities in local healthcare settings.